Lumenox: Aaru's Awakening - Burkni J. Óskarsson 1974-; Ingþór Hjálmar Hjálmarsson 1990-; Tyrfingur Sigurðsson 1989- (2012)
Printed version and artifacts are on a physical media, kept in Reykjavík University library. Aaru's Awakening is a mildly tactical, fast paced 2d action platformer with emergent gameplay mechanics. Aaru's Awakening features Aaru, the champion of Dawn and your goal is to prevent Night, an evil deity from devestating the Lumenox realm. The game utilizes the Unity3D game engine and the mechanics are written in C#, supported by a few javascripts and lower level code for shaders. The purpose of the project was to go through the game development process from beginning to end with the goal of productive development as if it was a retail product. We intended to create the best possible platformer we could make within our timeframe. A game with inspirational gameplay, intuitive graphics and the most dynamic puzzles. We want to give the gamers the experience of failure and hard earned wins leaving a lasting impression. The project was done in collaboration with Lumenox ehf who provided in game assets.